FILOSOFI MANUSIA SEBAGAI PENDIDIK - Rini Dewi Andriani; Saiful Akhyar Lubis; Candra Wijaya (Edukasi Islami: Jurnal Pendidikan Islam, 2015)
Talking about the educator, Islam is complete in describing an ideal educator figure, but still real and synchronized in every space and time. Prophet Muhammad Sholloulohu 'alaihi wa sallam is the figure of the ideal educator in any educational activities, both the material being presented, the method applied, or programmed curriculum. So that the learners who were born into a generation that was capable both in terms of cognitive, affective, psychomotor, and conative, so as to change the paradigm of civilization and distorted and underdeveloped. The idealism of the Prophet Muhammad as an educator this is the next level can be used as a reference for anyone who wants to become a full figure of educators who idealita but still reality, although of course absolutely not be able to equal it. In fact, this does not only apply to Muslims in particular, but also for other peoples. Because his message addressed to all mankind. Obviously, to be able to realize these ideals, can be reached by referring to al-Qur'an and the traditions of the Prophet Sholloulohu 'alaihi wa sallam, especially those associated with edukasinya life, because as the main source of Islam are authoritative and argumentative, certainly both discuss human philosophy as educators of the various aspects.Â Kata Kunci: Filosofi Manusia, Pendidik